Playing the Project: Incorporando a Gamificação em Abordagens Baseadas em Projetos para a Educação em Engenharia de Software - Souza, Maurício; Moreira, Renata; Figueiredo, Eduardo (Anais do Workshop sobre Educação em Computação (WEI); 2019: Anais do XXVII Workshop sobre Educação em ComputaçãoDO - 10.5753/wei.2019.6618, 2019)
In Software Engineering higher education, besides learning theory and acquiring technical skills, students need to develop the ability to apply, evolve, and practice those skills throughout their lifetime. From 2016 to 2018, we had been adapting an introductory Software Engineering course from a theory-oriented course to a more practical experience for students. Therefore, the goal of this paper is to describe our experience incorporating Project-based Learning (PBL) principles and gamification elements in practical assignments for SE education. To achieve this goal, we present the structure of PBL projects we have been using and how we adapted game elements to the context of SE education in order to create a gamified course. Based on our experience, we defined 17 guidelines that instructors may follow when defining a practical assignment for SE education. While PBL was helpful to create a practice-oriented teaching experience, gamification was not only useful in improving the engagement of students, but also in creating a roadmap of activities and a structure for students to self-assess their progress in the project.